Review of Translingual Dispositions: Globalized Approaches to the Teaching of Writing - Namubiru, Esther (Journal of Academic Writing, 2023)
In this review of Frost, Kiernan, and Malley's collection Translingual Dispositions: Globalized Approaches to the Teaching of Writing, I propose that the collection fills a necessary gap of augmenting translingualism discourse globally and beyond the classroom. The contributors to Frost, Kiernan, and Malley's collection develop the theory of translingualism as an attitude, lived experience, an advocacy issue, and a classroom practice by showing a myriad of application sites for this concept. In so doing, the collection also demonstrates the messy operationalization and embodiment of translingualism in U.S. academic and non-U.S. academic settings.